Economic voting - Dorussen, Han, 1962-; Taylor, Michaell (Routledge/ECPR studies in European political science ;, 2002)
This collection examines to what extents the economic situation is a decisive factor in dictating how people vote. The book combines theoretical work with empirical research and quantitative analysis.